Value Chain Strategy in Marketing: Turning Challenges into Opportunities in the Digital Age - Alwinda Manao; Agus Rahayu; Heny Hendrayati (Dinasti Publisher, 2025)
The digital era brings significant changes in the marketing landscape, requiring companies to adapt quickly to technological dynamics and changes in consumer behavior. This article aims to analyze the application of Value Chain Strategy in marketing and identify how this strategy can help companies turn challenges into opportunities in the digital era. This research uses a literature study approach by collecting and analyzing information from various relevant sources regarding the application of Value Chain Strategy and the challenges faced by companies in the digital era. The results show that companies that are successful in implementing Value Chain Strategy have integrated digital technologies, such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics, into every stage of the value chain. This helps increase efficiency, improve product quality, and strengthen relationships with suppliers and customers. However, challenges such as the need for adequate technology infrastructure, digital skills gaps, and resistance to change still need to be overcome. The implications of this study emphasize the need for companies to undertake comprehensive strategic change. Companies should invest in technological infrastructure and improve the digital skills of the workforce.